(untitled) (Revista Contexto & Saúde, 2020)
The objective of this study was to evaluate the association of inflammatory marker (PCRus) with the consumption of energy, fruits, legumes and vegetables in the elderly. The is a quantitative, descriptive and cross-sectional research, carried out in the city of Palmeira das Missões, Brazil, with the elderly aged over 60 years, totaling a sample of 43 elderly people. The sociodemographic information was obtained through an interview, held in the home of each elderly person, where they were instructed to attend with a 12-hour fasting, on scheduled day and time, a clinical analysis laboratory in the city, for collection of blood samples and anthropometric data. The present study showed higher frequency for no daily consumption of fruits (51.2%) and legumes and vegetables (58.1%), daily consumption of fruits, legumes and vegetables (FLV) below 3 servings (88.4%) and ultra-sensitive C-Reactive Protein over 0.3 mg/dl (51.2 %). In relation to sociodemographic data, according to the PCRus values, there was a statistically significant association with living without a partner (p=0.033). The energy consumption was low, as well as the mean consumption of fruits was below one serving per day (0.58 serving/day) and of legumes and vegetables (0.51 serving/day). The same low consumption occurred when grouped in FLV, which was below 3 servings per day with an average of 1.12 servings/day. Most of the elderly presented values of PCRus inflammatory marker above 0.3 mg/dl. There was a statistically significant relation between PCRus only with the marital situation of living without a partner.